WOMEN IN THE FULFILLMENT OF FAMILY LIVING MUBADALAH’S PERSPECTIVE - Burhanatut Dyana; Devi Eka Diantika (Profetika: Jurnal Studi Islam, 2023)
Divorce is a popular trend today. Every year, Indonesia has more divorces, and economic reasons are the main contributing cause. The rise of divorce has made Indonesia an emergency maslahat family. This research method is library research by making mubadalah as the primary source. According to mubadalah, the concepts of away and mu'asyarah bil ma'ruf transform the duty of life into a dual duty and responsibility. The duty to support oneself is based on one's qualities and capacities, not on one's gender, and in today's world, women have the same opportunities as men. It is hoped that divorce on financial grounds can be avoided when the husband and wife are aware of their respective roles, rights, and responsibilities and are supported by an understanding of Mubadalah. This is because they will be willing, understanding, supportive of, and able to care for one another.